Chemical composition of essential oils isolated from leaves, twigs, roots and cones of Vietnamese Keteleeria evelyniana Mast. Issue 2 (4th March 2022) - Thai, Tran Huy; Thi Hien, Nguyen; Cuong, Nguyen the; Casanova, Joseph; Tomi, Félix; Paoli, Mathieu
ABSTRACT: Keteleeria evelyniana Mast. is a species of conifer native to southern China, Laos and Vietnam. The species has been listed as vulnerable in Vietnam. Oil samples have been isolated from leaves, twigs, roots and cones, and analyzed by combination of GC(FID), GC-MS and 13 C NMR. The composition of leaf oil, dominated by α-pinene (37.8%) and β-pinene (17.9%), varied substantially from that previously reported. Twig, cone and root oil compositions are reported for the first time. Twig oil contained mainly (E)-β-caryophyllene (25.4%) accompanied by α-pinene (15.9%), limonene (15.4%). (E)-β-caryophyllene (40.8%) was predominant in root oil, followed by α-Pinene (27.9%) and α-humulene (8.1%). Lastly, the composition of cone oil was characterized by a high content of α-pinene (58.8%) followed by β-pinene (22.0%). The occurrence of the diterpene iso -abienol (1.3%) could be noted. It could also be highlighted that the conformers βα and ββ of (E)-β-caryophyllene have been evidenced by 13 C NMR spectroscopy.